Races of Fusarium oxysporum f. sp. lycopersici in tomato farmlands in San Luis Potosí - Hernández Martínez, Rosendo; López Benítez, Alfonso; Borrego Escalante, Fernando; Espinoza Velázquez, José; Sánchez Aspeytia, David; Maldonado Mendoza, Ignacio Eduardo; López Ochoa, Luis Alejandro (Revista Mexicana de Ciencias Agrícolas, 2018)
Wilting caused by Fusarium oxysporum f. sp. lycopersici (Fol) is one of the most important diseases of tomato (Solanum lycopersicum L.). Its pathogenic variability originated races 1, 2 and 3, as described in several countries. In Mexico has been reported in Sinaloa, Baja California Sur and Morelos. Tomato is a quite an important horticultural crop in Villa de Arista, San Luis Potosí, and for this reason, the aim of this study was to characterize pathogenicity tests by the variability in virulence of isolates of Fol in tomato farmlands of this region. 27 isolates of Fusarium oxysporum were gathered from tomato plants with characteristic symptoms of wilting of tomato plants in nine varieties of seven lots, which were processed in the laboratory to isolate the fungus, purify were obtained prepare inoculum and pathogenicity tests. Differential varieties used were Bonny Best susceptible to races 1, 2 and 3; Manapal resistant to race 1; Walter, resistant to races 1 and 2; I3R3 and resistant to races 1, 2 and 3. The races identified were race 2 in the Rafaello and Tipsey on the fields Agro Vida and Rancho el Clérigo, and race 3 in the varieties El Cid, Hannibal, and 77-05 in the farmlands San Gilberto, Santa María Elena and Lourdes. The identification of these breeds was made using the molecular technique of Chain Reaction (PCR) coincided with the results of tests pathogenic.
Keywords: Solanum lycopersicum L.; vascular Fusarium wilt; Fol races 2 and 3